2017
DOI: 10.1002/aur.1745
|View full text |Cite
|
Sign up to set email alerts
|

Atypical pupillary light reflex in 2–6‐year‐old children with autism spectrum disorders

Abstract: The purpose of this study was to investigate pupillary light reflex (PLR) in 2-6-years-old children with autism spectrum disorders (ASD). A total of 117 medication-free 2-6-year-old boys participated in this study. Sixty participants were diagnosed with ASD (the "ASD group") and the other 57 were in the control group of typical development (the "TD group"). A questionnaire was completed by the parent/guardian for assessing potential dysfunctions in the autonomic nervous system (ANS). The base pupil radius, PLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 38 publications
6
24
0
Order By: Relevance
“…The observation of latency decreasing with age was consistent with previous results reported in 2-to 6-year and 6-to 18-year old children of typical development 11,12 . Taken together, these data suggested that PLR latency decreases from 6 months old until 9~10 years old in the typically developing children.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The observation of latency decreasing with age was consistent with previous results reported in 2-to 6-year and 6-to 18-year old children of typical development 11,12 . Taken together, these data suggested that PLR latency decreases from 6 months old until 9~10 years old in the typically developing children.…”
Section: Discussionsupporting
confidence: 92%
“…The PLR constriction time was not correlated with latency and showed no significant age trend. The observation that base pupil size was larger in the HR group than in the LR group appeared similar to the difference previously reported between 2-year old children with ASD and those of typical development 12 . The observation of a smaller relative constriction in the HR group was similar to that observed in older children affected by ASD using a desktop PLR device 10,11 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Apart from localizing lesions that affect the Nervous System, certain parameters of pupil responsivity can also help diagnose disorders. Even at the early age of 2, children diagnosed with Autism Spectrum Disorder show increased baseline pupil diameter values [7] and diminished reactivity to simple visual stimuli [8].…”
Section: Introductionmentioning
confidence: 99%